Developing successful marketing strategies - Randazzo, Gary W. (Marketing strategy collection., 2014)
Uses real market examples to demonstrate the development of effective marketing strategies. The approach uses an organization's mission and vision statements to guide the development of marketing goals, strategies, and tactics. Central to the development of marketing strategy is the use of the marketing mix of price, place, product, and promotion. The book neatly weaves the process of developing a marketing strategy with the use of the marketing mix. Throughout the book examples are given to clarify the theories and guide the reader through the strategic marketing planning process. Managers and executives will use this book as a guide to grow an established business or start a new one. The book can be used as a reference book for unique marketing challenges as well.